Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2000
DOI: 10.1016/s0893-133x(99)00150-5
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Serotonin and Serotonergic Agonists and Antagonists on the Production of Interferon-γ and Interleukin-10

Abstract: (5-HT) is a neurotransmitter and an immune modulator. In vitro , antidepressants with a serotonergic mode of action have, at concentrations within the therapeutical range, negative immunoregulatory effects, i.e., they increase the production rate of interleukin-10 (IL-10), a negative immunoregulatory cytokine. We have hypothesized that part of these effects may be explained by the serotonergic activities of antidepressants on immunocytes. This study was carried out to examine the effects of 5-HT, p-chloropheny… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
43
0
1

Year Published

2000
2000
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(44 citation statements)
references
References 43 publications
0
43
0
1
Order By: Relevance
“…Other routes than IDO / TDO proinflammatory cytokines may also be involved in changes in NA and 5-HT. Inflammatory cytokines may directly affect 5-HT turnover (reuptake and degradation) as well as receptor distribution and sensitivity in brain regions presumed to be involved in depression such as hypothalamus, hippocampus, amygdala and prefrontal cortex [123,[145][146][147][148][149], reinforcing the IDO / TDO mediated effect on serotonin.…”
Section: Ido and Tdomentioning
confidence: 99%
“…Other routes than IDO / TDO proinflammatory cytokines may also be involved in changes in NA and 5-HT. Inflammatory cytokines may directly affect 5-HT turnover (reuptake and degradation) as well as receptor distribution and sensitivity in brain regions presumed to be involved in depression such as hypothalamus, hippocampus, amygdala and prefrontal cortex [123,[145][146][147][148][149], reinforcing the IDO / TDO mediated effect on serotonin.…”
Section: Ido and Tdomentioning
confidence: 99%
“…Although our laboratory has previously shown that fluoxetine will decrease splenic lymphocyte proliferation in vitro at higher doses [34], it is not likely that the effects of fluoxetine observed in vivo are due to direct effects of fluoxetine on immune cells, since suppression is observed only in animals with an intact serotonergic system. However, fluoxetine might be acting in the periphery to modulate immune cell function through elevations in plasma or local serotonin levels, since serotonin has been shown to decrease immune cell function at higher concentrations, when applied to immune cells in vitro [45,[64][65][66]. Another possibility is that elevations in central serotonin levels following fluoxetine resulted in activation of CNS modulatory systems.…”
Section: Discussionmentioning
confidence: 99%
“…These drugs bind to other receptors that could interfere with proliferative responses, such as H 1C histamine receptors [36] and ion channels, including potassium, calcium and sodium [37][38][39][40][41][42][43][44]. One example, the SSRI, sertraline, has been shown to decrease the IFNÁ/IL-10 ratio by increasing IL-10 secretion [35], whereas 5-HT also decreases the IFNÁ/IL-10 ratio but it does so by decreasing IFNÁ rather than increasing IL-10 secretion [45]. Therefore, it appears that the effects of sertraline on production of these cytokines are not related to its serotonergic activity.…”
Section: Introductionmentioning
confidence: 99%
“…Although thus far the localization of these 5-HT receptor subtypes in the brain is largely unknown and further studies are ongoing to better 2-Aminotetraline in ischemic injury C Capone et al define their specific function (Leysen, 2004), these data indicate that they may be involved in the control of inflammatory molecule release. Actually serotonin is known to be involved in a wide spectrum of immune response modulatory activity (Hellstrand et al, 1993;Kubera et al, 2000Kubera et al, , 2005Young and Matthews, 1995). Interestingly, one recent study proposes a specific involvement of 5-HT2B receptors in the regulation of inflammatory cytokine production from blood cells (Kubera et al, 2005), and a second one shows that stimulation of 5-HT2B receptors leads to a TNF-a converting enzyme-dependent TNF-a release, thus linking activation of these receptors to an increased expression of pro-inflammatory cytokines (Pietri et al, 2005).…”
Section: -Aminotetraline In Ischemic Injurymentioning
confidence: 99%